13. MENINGKATKAN KUALITAS SUMBER DAYA MANUSIA MELALUI ORGANISASI PEMBELAJARAN - Farida, Naili (FORUM, 2008)
Learning Organisation is an organisation aim for capacity building, self adjusment and continuosly changing to keep up with enviroment dynamic change and guarantee organisation longetivity learning model can be conducted within group or team or units within organisation and individual is a process achieved by person throuh learning to improve human resource capacity. To create learning organisation it takes five elements, the are : individual skill, vision, metal model, learning team and thinking sytem. Therefor organisation will be able to accept futureÂ  challenge.